Lilen San Juan: The Light Of Social Cohesion and Religious Moderation - Woho Atasoge, Anselmus Dore; Nuwa, Damianus Dionisius; Sengga, Fransiskus Yance; Mulan Kabelen, Mikael Alfianus; Watu, Christianus (Pascasarjana IAIN Pontianak, 2025)
The rituals and the symbols embedded therein serve as markers of national identity and sources of inspiration for harmony within Indonesia’s multi-religious society. The researcher posits that the San Juan ritual and its accompanying symbols function as mediums for fostering social cohesion and hold significant implications for the promotion of religious moderation in Indonesia. This study seeks to explore the spiritual significance of the San Juan ritual as a contribution to the formation of a cohesive society grounded in the principles of religious moderation. The study adopts an anthropological and sociological approach. Data were obtained through field observations and structured interviews with 25 informants, including cultural leaders, religious leaders, government officials, educators, and youth. The data were analyzed in three stages: data reduction, data presentation, and data verification, utilizng two analytical techniques—descriptive analysis and content analysis. The analysis of the rituals, their symbols, and the behavior of ritual participants is key to understanding the social structures and processes, as well as the broader social phenomena at play. This study finds that, in light of Victor Turner’s theoretical framework, the San Juan ritual—especially the candle (lilen) as its central symbol—serves both to reinforce the identity of the San Juan community and to act as a conduit for fostering social cohesion that supports religious moderation in Indonesia. This implicational meaning also contributes to the scholarly discourse in the sociology and anthropology of religion.